5-ALA fluorescence based isolation of minority population GBM cells identifies putative invasion associated molecular changes. (31st January 2018) - de los Angeles Estevez-Cebrero, Maria; Lourdusamy, Anbarasu; Rahman, Ruman; Smith, Stuart
Abstract: INTRODUCTION: Glioblastoma (GBM) is a highly pleomorphic polyclonal tumour with molecular abnormalities varying temporo-spatially (intra-tumour heterogeneity), one mechanism of therapy resistance. Fluorescence guided resection (FGR) is performed with prior administration of 5-aminolevulinic acid (5-ALA) leading to individually fluorescent tumour cells mixed within a background population of non-neoplastic neural cells in the invasive region beyond the "pure" tumour. We have isolated this invasive tumour population by fluorescence activated cell sorting (FACS) to allow the study of invasive tumour cells without an overwhelming background "normal" signal. We conducted genome wide gene expression of phenotypically distinct areas of the tumour and from fluorescent/non-fluorescent cancer/non-cancer cells purified from the invasive zone respectively. METHODS: We performed genome-wide gene expression analysis on 14 glioma samples from three different GBM patients including samples from tumour core, rim, invasive margin and GBM cells from the invasive margin that were isolated by 5-ALA assisted FACS. RESULTS: Statistical analysis by linear models for microarray data identified 325 differentially expressed genes between FACS positive cells and other tumour regions (adjusted P-value < 0.05), of these, 50 genes were upregulated in all comparisons. These transcriptomic changes orchestrate MAPK (DUSP1, DUSP2, DUSP10 and FOSB), chemokine signalling pathways (CXCL2, CXCL3, CCL20 and NFKB1) and negative regulation of cell proliferation (EREG and KLF6). In contrast, 29 downregulated genes in FACS positive cells were enriched with signal transduction (DDR2 and MTSS1L) and ECM-receptor interaction (COL4A1, COL4A2, and HSPG2). DISCUSSION: Residual cells responsible for GBM recurrence in the invasive zone are shown to be not only phenotypically different but also exhibiting activation of distinct molecular pathways and biological processes. These unique molecular features offer hope for developing more efficacious targeted therapies focusing on this population rather than the bulk tumour that has been the subject of most historical analyses.